WASATHIYYAH DI TENGAH BADAI: MENJAGA MODERASI BERAGAMA DI ERA POLARISASI - Fauziyah, Hana; Afiyatun Kholifah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Abstract: Religious moderation is becoming increasingly relevant in an era of polarization marked by ideological conflict, identity politics, and the rise of hate speech on social media. The concept of wasathiyyah in Islam, which emphasizes moderation, tolerance and balance, offers a solution to maintain harmony in diversity. This article examines the importance of religious moderation as a strategy to reduce extremism and liberalism that threaten social cohesion in Indonesia. Using a qualitative approach, the article analyzes the challenges of religious moderation in the digital era, including the spread of hoaxes and intolerant narratives, and explores concrete efforts such as the Religious Moderation Village program and creative initiatives such as the Religious Moderation Film Festival. The results show that the implementation of wasathiyyah through education, interfaith dialogue, and media literacy can strengthen tolerance and prevent polarization. This article recommends strengthening collaboration between the government, religious communities, and civil society to promote religious moderation as a pillar of inclusive and peaceful national life. Keywords: religious moderation, wasathiyyah, polarization, tolerance, extremism, social media, diversity, social cohesion